The contribution of coastal women to enhance family economics: Case Study of the Ayau Islands, Raja Ampat Regency, West Papua Province - Suruwaky, Amir M.; Handayani, Handayani; Leiwakabessy, Ivonne M.; Ratna, Ratna; Munzir, Munzir; Syahrul, Syahrul; Fauzi, Nasrul; Saputro, Roman Hadi; Potolau, Michel Jacson Nalawo; Hismayasari, Intanurfemi B. (Sangia Research Media and Publishing, 2024)
The contribution of women in fisheries at the Ayau Archipelago is vital, this evidence can be regarded in their important role in family. This study aims to examine the contribution of coastal women in improving family economics. The methods used are interviews and Focus Group Discussions (FGD). Our study revealed that their level education are mostly at elementary graduates. Our compiled data analysis listed that their low level graduation are shown in the following list: Meosbekwan Village 60%, Rutum 67%, Abidon 100% and Reni 88%. In addition, they are housewives and helping husband in the various role in order to have additional incomes by producing salted fish, dry sea cucumbers, and sea worms product. Finally, they performed a significant alternative income between IDR 3,000,000 and IDR 5,000,000.00 per month.